Hapten-specific T-cell responses to 4-hydroxy-3-nitrophenyl acetyl. II. Demonstration of idiotypic determinants on suppressor T cells (The Rockefeller University Press, 1979)
The ability of NP-coupled syngeneic spleen cells to induce antigen- specific T-suppressor cells capable of binding to NP-BSA-coated Petri dishes and mediating transfer of specific suppressive activity to NP was demonstrated. Furthermore, in strains of mice bearing the Ig-1b allotype, including SJL, and in (non-Ig-1b x Ig-1b)F1 hybrids, the NP- specific suppressor cells also interferes with expression of immunity after priming with NIP-BGG. Anti-NPb anti-idiotype antiserum plus complement treatment effectively abrogated the ability to transfer suppression. Formal genetic mapping of the fine specificity of cross- reactivity with Ig-1 allotypic congenic mice implies that expression of this trait is linked to the Ig-1b heavy chain linkage group. The sensitivity of NP-suppressor cells of appropriate strains to anti- idiotype treatment was also consistent with the formal mapping data. These experiments suggest that there are shared V-region structures on antibody and T cells that are crucial in the suppression pathway for the same antigen.